Avaliação das contribuições da coleta seletiva solidária do PROGERE/UFC junto a associações de catadores de materiais recicláveis de Fortaleza-CE - Almeida, Gerlania Félix de (2022)
The problem of solid waste follows the human civilization process. In view of the resulting environmental problems, aiming at achieving sustainable development, public policies for waste management emerge with great relevance. Within Higher Education Institutions, environmental waste management relies on the Solidarity Selective Collection, an instrument that has the ability to, in addition to waste management, foster associations of collectors. In this line, the present research had as general objective to evaluate the Solidarity Selective Collection of the Solid Waste Management Program of UFC regarding its contributions with the associations of recyclable collectors registered in the program. This assessment was based on the Collective Subject Discourse (LEFÈVRE; LEFÈVRE, 2005). Methodologically, a qualitative approach was carried out, with quantitative contributions, in addition to bibliographic research and semi-structured interviews with recyclable material collectors from associations registered in PROGERE. The total number of people interviewed was 10 (ten), belonging to 04 (four) associations of collectors of recyclable materials in Fortaleza-CE, with 100% of the sample being female. All the interviewees work informally in the associations. Regarding marital status, 40% (4) of the interviewees are married and 60% (6) are single. Furthermore, 100% of the interviewees have children. The average is 3 (three) children, with a minimum number of 1 (one) child and a maximum of 5 (five) children. The mean age was 49.9 years, with a minimum age of 28 years and a maximum age of 60 years. Furthermore, it was identified that 60% (6) of the interviewees had only completed elementary school, all incompletely. Only 30% (3) of the interviewees completed high school, and only 2 (two) did it on a regular basis, and 10% (1) completed it through government programs, such as the Education of Youth and Adults (EJA) ). As for time in the profession, the average number of years is 20.1 years, with the minimum time being 3 (three) years and the maximum time being 34 (thirty-four) years. As for the age at which you started working as a recyclable collector, the average age is 29.8 years, with a minimum age of 9 (nine) years and a maximum of 44 (forty-four) years. In relation to the monthly income acquired in the association, the average is R$ 523.80, with a minimum income of R$ 200.00 reais and a maximum income of R$ 1,000.00 reais. In this aspect, it was observed that collectors obtain higher income when linked to larger associations, with better organization and greater structuring. The evaluation results were obtained with the interpretation of four Discourses of the Collective Subject. Thus, it was found that the interviewees have a good opinion about the quality of the materials coming from the program, as well as saying that the Solidarity Selective Collection of PROGERE contributes to improving the work in their associations. However, there was a need to expand the Selective Collection to other UFC campuses, as well as the absence of a fixed point for collecting materials. Also, limitations in communication between PROGERE and associations were identified.